2021
DOI: 10.1093/jas/skab156
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and postmortem meat quality in crossbred lambs

Abstract: The objective of this study was to evaluate effects of different levels of lipopolysaccharide (LPS)-mediated oxidative stress on fresh meat quality. Crossbred lambs (n = 29) were blocked by weight and fed a standard finishing ration for the duration of the study. Lambs were individually housed and treatment groups were administered one of three intravenous injections every 72 h across a three-injection (9-day) cycle: saline control (Control), 50 ng LPS/kg bodyweight (BW) (LPS50), or 100 ng LPS/kg BW (LPS100). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Conversely, Chen et al (2021) demonstrated that ROS accumulation ameliorates the meat texture via inducing satellite cell proliferation and collagen synthesis in grass carp muscle. In addition, several studies suggested that ROS, especially hydrogen peroxide (H 2 O 2 ), acts as a secondary messenger molecule to activate apoptosis and caspase-3, which is conducive to the tenderization of lamb and bovine muscle ( Herrera et al, 2021 , Ma et al, 2022 , Wang et al, 2018 ). According to the above literature, there is inconsistency in describing the influence of ROS on meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Chen et al (2021) demonstrated that ROS accumulation ameliorates the meat texture via inducing satellite cell proliferation and collagen synthesis in grass carp muscle. In addition, several studies suggested that ROS, especially hydrogen peroxide (H 2 O 2 ), acts as a secondary messenger molecule to activate apoptosis and caspase-3, which is conducive to the tenderization of lamb and bovine muscle ( Herrera et al, 2021 , Ma et al, 2022 , Wang et al, 2018 ). According to the above literature, there is inconsistency in describing the influence of ROS on meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…During the cultivation of goslings, feed corruption and poor breeding environment could cause widespread bacterial infection. This phenomenon will increase blood levels of endotoxin lipopolysaccharide ( LPS ) in goslings, and LPS exposure could greatly impact both product quality and consumer palatability ( Herrera et al, 2021 ). More importantly, LPS could stimulate the innate immunity and trigger biochemical and cellular responses that lead to the inflammation and toxicity ( Kolomaznik et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%